Heat and mass transfer analysis in air gap membrane distillation process for desalination - Pangarkar, Bhausaheb L.; Sane, Mukund G. (Membrane Water Treatment, 2011)
The air gap membrane distillation (AGMD) process was applied for water desalination. The main objective of the present work was to study the heat and mass transfer mechanism of the process. The experiments were performed on a flat sheet module using aqueous NaCl solutions as a feed. The membrane employed was hydrophobic PTFE of pore size 0.22 mu m. A mathematical model is proposed to evaluate the membrane mass transfer coefficient, thermal boundary layers' heat transfer coefficients, membrane/liquid interface temperatures and the temperature polarization coefficients. The mass transfer model was validated by the experimentally and fitted well with the combined Knudsen and molecular diffusion mechanism. The mass transfer coefficient increased with an increase in feed bulk temperature. The experimental parameters such as, feed temperature, 313 to 333 K, feed velocity, 0.8 to 1.8 m/s (turbulent flow region) were analyzed. The permeation fluxes increased with feed temperature and velocity. The effect of feed bulk temperature on the boundary layers' heat transfer coefficients was shown and fairly discussed. The temperature polarization coefficient increased with feed velocity and decreased with temperature. The values obtained were 0.56 to 0.82, indicating the effective heat transfer of the system. The fouling was observed during the 90 h experimental run in the application of natural ground water and seawater. The time dependent fouling resistance can be added in the total transport resistance.
Keywords: AGMD; Desalination; heat transfer coefficient; mass transfer coefficient; temperature polarization coefficient

Status of membrane distillation for water and wastewater treatment-a review - Pangarkar, Bhausaheb L.; Sane, Mukund G.; Parjane, Saroj B.; Guddad, Mahendra (Desalination and Water Treatment, 2014)
Membrane distillation (MD) is a promising separation technique for water treatment. It is a nonisothermal process known since 1963. However, this technology still needs to be developed for its industrial implementation for different purposes. This paper presents a status review of MD based on the available published literatures and on preliminary analysis. The review covers the concept, membranes and modules design, configurations, performance parameters, fouling phenomena, the heat and mass transfer phenomena, applications, energy assessment, heat integration, and Memstill technology of MD process. Earlier study indicates that the permeate quality obtained by MD is stable and practically independent on the feed concentrations. The permeate flux is strongly affected by the feed temperature, feed flow rate, vacuum pressure in vacuum MD, and the boundary layer heat transfer coefficient. The permeate flux obtained in the literature of MD process is disagree by an order of enormity and hence better experimental work is needed. The less attention was found in the literature towards the removal of organic and inorganic toxic constituents from the groundwater by MD process.
Keywords: Fouling; Membrane configuration; Membrane design; Membrane distillation; wastewater